1)
Để n + 2 \(⋮\)(n - 3)
=> (n-3) + 5 \(⋮\)(n - 3)
=> 5 \(⋮\)(n - 3)
=> (n - 3) \(\in\)Ư(5)={1; -1; 5; -5}
=> n \(\in\){4; 2; 8; -2}
Vậy...
\(n+2⋮n-3\)
\(\Leftrightarrow n-3+5⋮n-3\)
\(\Leftrightarrow5⋮n-3\)
Ta có bảng
n - 3 | -5 | -1 | 1 | 5 |
n | -2 | 2 | 4 | 8 |
Vậy ..........
Bài 2,a,\(A=\left(-a-b+c\right)-\left(-a-b-c\right)\)
\(=-a-b+c+a+b+c\)
\(=2c\)
b, khi a = 1 ,b = - 1 , c = - 2 thì A = 2 . (-2) = -4
2)
a, A = (-a - b + c ) - ( -a - b - c )
A = -a -b + c + a + b + c
A = 2c
b, Thay a = 1 ,b = - 1 , c = - 2 vào A, ta có:
A = 2c = 2. (-2) = -4
Vậy...
Chúc em học tốt!!!
1)
Để n + 2 ⋮(n - 3)
=> (n-3) + 5 ⋮(n - 3)
=> 5 ⋮(n - 3)
=> (n - 3) ∈Ư(5)={1; -1; 5; -5}
=> n ∈{4; 2; 8; -2}
Vậy...